Merle the high flying squirrel. - Peet, Bill. (Boston, Houghton Mifflin, 1974)
Unhappy about the noise and clutter of the city, a squirrel travels west to find peace and quiet in the forest of giant trees he has heard about.
Keywords: Squirrels -- Fiction